PENGARUH KREDIBILITAS ENDORSER LOKAL TERHADAP IKLAN KOSMETIK DAN MINAT BELI KONSUMEN - rahmania, alvi; Fadli (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2021)
ABSTRACT The credibility of local endorsers is one of the factors to rely on the truth of the message that the advertisers convey, whose ad targets are local people. Cosmetics advertisements are a means of communication for products delivered through social media to attract the consumer buying interest. The purpose of this study was to determine whether the local endorsers’ credibility on cosmetic advertisement affected the consumers’ buying interest. This research was a survey. The sample comprised 92 respondents, Year-11 students of SMA Negeri 1 Sungai Raya Kepulauan, Bengkayang Regency, West Kalimantan, selected using purposive sampling technique.The data were collected with a google form delivered through online access, and they were analyzed quantitatively. The results showed that the significance value of the local endorser credibility variable (X) on the cosmetic advertising variable (Y1) in the coefficients table was 0.000 <0.05 and the count value was 8.768> 1.990, and the influence of the local endorser credibility variable on the cosmetics advertising variable was 46.0. %, categorized sufficient, while the result of the local endorser credibility variable test (X) on the purchase intention variable (Y2) was significant 0.000 <0.05 and count of 4.170> 1.990, and the influence of the variable was 16.2%, categorized low but definite. The conclusion of this study is that there is an influence of local endorsers’ credibility on cosmetic advertising and consumer buying interest.